The role of teledentistry in promoting oral health and preventing disease among the elderly - Shuwen Pang; Hua Li; Xia Zeng; Hua Lei; Yinxia Luo; Shuang Zhang (Guoji laonian yixue zazhi)
Teledentistry integrates advanced telecommunications technology with dental care through the use of electronic health records, electronic referral systems, digital imaging, remote consultations, and remote diagnostics.It finds extensive application in preventive dentistry, orthodontics, endodontics, oral surgery, periodontal disease management, early cavity detection, patient education, dental medicine, and diagnostic practices.This review offers a comprehensive overview of teledentistry, detailing its service types, current applications, and limitations in enhancing and preventing oral health issues among the elderly within our country.The objective is to outline future prospects for elderly oral healthcare in China and provide a valuable reference for subsequent clinical initiatives.